Growth Based Strategy Formulation for Selection of Murrah Buffalo at Early Ages - Gupta, Jay Prakash; Sachdeva, Gulshan Kumar; Gandhi, Ravinder Singh; Wakchaure, Rajesh Sudhakar; Chakravarty, Atish Kumar (Journal of Advanced Veterinary Research, 2011)
Buffaloes form the backbone of farmers in Indian dairy industry. The birth weight and weight at different age of an animal characterizes expression of animals’ genotype and serves as reliable aid to selection for efficient performance of livestock. The data on body weight were collected on 726 new born female calves and 642 male calves of livestock farm, NDRI, Karnal. Growth curves for both male and female buffalo calves were prepared by plotting mean of the body weight against age in weeks and Growth band were prepared by computing upper and lower limits of average body weights (95% confidence limit), from birth to 6 month of age, at weekly interval. The growth curves were found to be linear for both male and female buffalo calves. Growth band was narrow at the birth, but it goes on widening with age at successive weeks. The presentation of growth band is expected to be useful in making an efficient decision for proper management of animals at various ages.